Peningkatan Kemampuan Mengenal Angka Melalui Permainan Bowling Angka di PAUD Kasih Ibu Kota Sawahlunto - Restu Asriya, Fitri; Marlina, Serli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
ABSTRACT This research began with the fact that at the Kasih Ibu Sawahlunto PAUD, the ability to recognize numbers was still low, especially in recognizing or stating the sequence of numbers in children aged 4-5 years. The aim of this research is to see whether the number bowling game can improve the ability to recognize numbers. The benefits of researchers are for students, for teachers, researchers at PAUD Kasih Ibu. The type of research is Classroom Action Research (PTK) with the research subject being Early Childhood Education, Mrs. Sawahlunto, aged 4-5 years, with 8 children, 3 boys and 5 girls. The techniques used in data collection are observation and documentation. Next, the percentage technique is processed. This Classroom Action Research was carried out in 2 cycles. Cycle I consists of 3 meetings and cycle II consists of 3 meetings. The results of research in each cycle have shown an increase in the ability to recognize numbers, from cycle I consisting of 3 meetings where in the initial conditions the average BSB value was 0%, cycle II BSB increased to 25%, then continued in cycle II with an increase in the ability to recognize numbers on average. the average reached 83.3%, which means it has exceeded the Completeness Criteria. Minimum (KKM) is 75%. Based on the research results, it can be concluded that the number bowling game can improve the ability to recognize numbers in the Kasih Ibu Sawahlunto PAUD.